Hepatoceliulinės karcinomos prognostinės sistemos - Jonas Pivoriūnas; Jonas Jurgaitis; Marius Paškonis; Agnius Juška; Janina Didžiapetrienė; Eugenijus Stratilovas; Narimantas Evaldas Samalavičius; Vitalijus Sokolovas; Gintautas Brimas; Kęstutis Strupas (Lietuvos Chirurgija, 2008)
Jonas Pivoriūnas1, Jonas Jurgaitis2, 3, Marius Paškonis2, 3, Agnius Juška1, Janina Didžiapetrienė3, Eugenijus Stratilovas3, Narimantas Evaldas Samalavičius3, Vitalijus Sokolovas3, Gintautas Brimas2, Kęstutis Strupas2 1 Vilniaus universiteto Medicinos fakultetas, M. K. Čiurlionio g. 21, LT-03101 Vilnius 2 Gastroenterologijos, urologijos ir abdominalinės chirurgijos klinika, Vilniaus universiteto ligoninės Santariškių klinikos, Santariškių g. 2, LT-08661 Vilnius 3 Vilniaus universiteto Onkologijos institutas Santariškių g. 1, LT-08660 Vilnius El paštas: jonas.jurgaitis@santa.lt